Paradox Role of Oxidative Stress in Cancer: State of the Art - Cinzia Domenicotti; Barbara Marengo (MDPI AG, 2022)
The modulation of oxidative stress is essential for the maintenance of redox homeostasis in healthy and cancer cells [...]